Managing intellectual property in a collaborative environment: learning from IBM. (7th May 2007) - Bader, Martin A.
This paper outlines the increasing importance that intellectual property has achieved in inter-firm research and development collaborations with respect to the new economy industry sector. It is based on an explorative, case study-based research approach that was chosen because of the novelty of managing intellectual property in research and development collaborations as an empirical phenomenon. Starting from theoretically derived core components for managing intellectual property in research and development collaborations, this contribution analyses successful practices of a leading information technology and service innovation company, namely IBM, within the new economy sector. The paper concludes with a procedural model for managing intellectual property by asserting that its consideration is essential in conducting and exploiting a sustainable collaboration.